2009
DOI: 10.1073/pnas.0812880106
|View full text |Cite
|
Sign up to set email alerts
|

FGF-dependent left–right asymmetry patterning in zebrafish is mediated by Ier2 and Fibp1

Abstract: Establishment of left-right asymmetry in vertebrates requires nodal, Wnt-PCP and FGF signaling and involves ciliogenesis in a laterality organ. Effector genes through which FGF signaling affects laterality have not been described. We isolated the zebrafish ier2 and fibp1 genes as FGF target genes and show that their protein products interact. Knock down of these factors interferes with establishment of organ laterality and causes defective cilia formation in Kupffer's Vesicle, the zebrafish laterality organ. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 48 publications
7
83
2
1
Order By: Relevance
“…Recent studies have shown that FGF signaling is required for morphogenesis and ciliogenesis of the KV as well as for LR patterning (2,8,15). Although knockdown of the FGF target genes ier2 and fibp1 is known to interfere with DFC formation (15), the contribution of FGF signaling before KV formation is poorly understood.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have shown that FGF signaling is required for morphogenesis and ciliogenesis of the KV as well as for LR patterning (2,8,15). Although knockdown of the FGF target genes ier2 and fibp1 is known to interfere with DFC formation (15), the contribution of FGF signaling before KV formation is poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulated evidence points to crucial roles of FGF signaling in several processes of LR asymmetric patterning (2,8,9,15,21,22). Two recent studies, in particular, have shown that FGF signaling regulates KV ciliogenesis during LR pattering (8,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ier2 expression also correlates with cell differentiation, for example, during neuronal differentiation of PC12 and H19-7 cells (Charles et al, 1990;Eschelbach et al, 1998;Chung et al, 1998), and after TPA-induced differentiation of HL-60 cells (Shimizu et al, 1991). During embryonic development, Ier2 has been reported to determine left-right asymmetry patterning in an fibroblast growth factor (FGF)-dependent manner through interacting with fibp1 (Hong and Dawid, 2009). …”
Section: Ier2 Expression Promotes Invasiveness Of 1as Tumor Cellsmentioning
confidence: 99%